2011
DOI: 10.1590/s1679-45082011ao2006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: five-year experience at a University Hospital

Abstract: This set of cases from a tertiary public healthcare service reflect the approach of multiple myeloma in a predominantly young population with advanced clinical staging, with results comparable to those of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Multiple myeloma bone lesions arise from altered bone remodeling due to both increased osteoclast activation and decreased osteoblast differentiation. 15 Bone involvement in our study is in concurrence with the study conducted by Todaro et al, 14 who found 74% of patients of multiple myeloma had osteolytic lesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple myeloma bone lesions arise from altered bone remodeling due to both increased osteoclast activation and decreased osteoblast differentiation. 15 Bone involvement in our study is in concurrence with the study conducted by Todaro et al, 14 who found 74% of patients of multiple myeloma had osteolytic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of renal involvement is slightly higher in studies conducted by Dawson et al and Kyle et al, who have found an incidence of 45% and 55%, respectively. 13 Hypercalcemia was found in 32% of patients in our study, which is comparable to the study done by Vahini et al 9 and Todaro et al 14 In our study, 73% of patients had osteolytic lesions showing varied skeletal involvement in radiological investigations. Bone disease in multiple myeloma results in severe bone pain, pathological fractures, and hypercalcemia.…”
Section: Discussionsupporting
confidence: 90%
“…In Brazil, the mean age at diagnosis is 10 years lower than those reported in published literature, and this fact can be explained given that the most of diagnoses occur at advanced stages. (4,5) The clinical presentation of MM is variable, and the chain of myeloma development, which possibly begins from monoclonal gammopathy, may be mediated by a condition called "smoldering myeloma". This, as suggested by its name, does not present symptoms despite the presence of 10% plasma cells and evidence of a monoclonal protein (diagnostic criterion).…”
Section: ❚ Introductionmentioning
confidence: 99%